2009
DOI: 10.1108/00220410910998906
|View full text |Cite
|
Sign up to set email alerts
|

Linking folksonomy to Library of Congress subject headings: an exploratory study

Abstract: Purpose -The purpose of this paper is to investigate the linking of a folksonomy (user vocabulary) and LCSH (controlled vocabulary) on the basis of word matching, for the potential use of LCSH in bringing order to folksonomies. Design/methodology/approach -A selected sample of a folksonomy from a popular collaborative tagging system, Delicious, was word-matched with LCSH. LCSH was transformed into a tree structure called an LCSH tree for the matching. A close examination was conducted on the characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 12 publications
2
74
0
Order By: Relevance
“…Yi and Chan () chose to ignore subdivided authority records because they felt that associating a subdivided authority record with its main heading would not reflect a true broader relation (Yi & Chan, ). Our position is that the LCSH structure should reflect the existence of some kind of relation between a main heading and its subdivided versions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yi and Chan () chose to ignore subdivided authority records because they felt that associating a subdivided authority record with its main heading would not reflect a true broader relation (Yi & Chan, ). Our position is that the LCSH structure should reflect the existence of some kind of relation between a main heading and its subdivided versions.…”
Section: Discussionmentioning
confidence: 99%
“…The LCSH hierarchy cannot be called a tree since it does not adhere to these structural rules. Specifically: it is a set of independent branches without a common root node (Yi & Chan, ); in other words, there is a large number of orphan authority records that have no connection to the structure (see review by Shubert, ; Sinkankas, ); main headings often have multiple parents; it may contain cycles. …”
Section: Introductionmentioning
confidence: 99%
“…Similar searches across library and information science literature turn up some explorative research on the possibilities of mapping LC data, but again no animated stack maps are found. 4 There is a product licensed by Bowker Inc. called StackMap that can be linked to catalog search results. When a user clicks on the map link next to a call number result, a map is displayed with the destination stack highlighted, but the information provided is locational only.…”
Section: Other Stack Maps and Related Technologiesmentioning
confidence: 99%
“…Explicit semantic analysis (ESA) uses concept vector representation to explicitly represent the meanings of a text fragment. Similar techniques were used by other researchers for solving practical problems such as synonymy and polysemy, bringing order to folksonomies (user vocabulary), learning personalized ontology, and document summarization . That is, conceptual annotation can help a user to have a rough idea about the hidden meanings of the discovered patterns.…”
Section: Introductionmentioning
confidence: 97%